Chronic Pancreatitis - Indira Kemalasari; Murdani Abdullah; Marcellus Simadibrata (The Indonesian Journal of Gastroenterology, Hepatology, and Digestive Endoscopy, 2018)
Chronic pancreatitis is a progressive inflammation in pancreas results in fibrosis and irreversible damage lead to loss of exocrine and endocrine function. Mortality and complication rate is high. Appropriate management of chronic pancreatitis begin from accurate diagnosis to adequate treatment. Diagnosis is still a challenge for clinician, mostly in early-stage disease. Several diagnostic modalities such computed tomography scan, magnetic resonance cholangiopancreaticography, endoscopic ultrasound, endoscopic retrograde cholangiopancreaticography, and direct-indirect pancreatic function test help diagnosis establishment. Endoscopic approach has an important role, both during diagnosis and treatment.